Democratization and development The case of Quinabut-an Irrigatiors Association. - Cabañezas, Vicente D. (Tacloban City Vicente D. Cabañezas, 2009)
This study is about a particular irrigators association. This study aimed to examine this cooperative in the context of democratization and development. Given the situation of the research subject and in consideration to the research locale, this will elevate a primary level organization into the realm of national cooperativism, democratization, and development.
Moreover, this study was guided by cooperative principles according to the Rochdale Principles which was authored by the Rochdale Pioneers. These cooperative principles are: open and voluntary membership, democratic control, limited interest of capital, patronage refund, continuous education and training, and cooperation with other associations with similar interests. Interpretations of these keywords are discussed thoroughly in the succeeding chapters of this paper.
These variables serve as the indicators in situating the Quinabut-an Irrigators Association in the context of democratization and development.
Several related literatures proved the dynamics of democratization and development. These principles are profound indicators of cooperativism. Similar cases were studied by reputable authors and have concluded national and global recognition and emphasis on the two principles.
Undergraduate thesis (B.A.S.S. Political Science)--University of the Philippines, Tacloban.
Keywords: Social Science